2020
DOI: 10.1038/s41467-020-19503-4
|View full text |Cite
|
Sign up to set email alerts
|

Mus81-Mms4 endonuclease is an Esc2-STUbL-Cullin8 mitotic substrate impacting on genome integrity

Abstract: The Mus81-Mms4 nuclease is activated in G2/M via Mms4 phosphorylation to allow resolution of persistent recombination structures. However, the fate of the activated phosphorylated Mms4 remains unknown. Here we find that Mms4 is engaged by (poly)SUMOylation and ubiquitylation and targeted for proteasome degradation, a process linked to the previously described Mms4 phosphorylation cycle. Mms4 is a mitotic substrate for the SUMO-Targeted Ubiquitin ligase Slx5/8, the SUMO-like domain-containing protein Esc2, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…Interestingly, the presumed S. cerevisiae Rad60 ortholog Esc2 has been reported to interact with Mus81 via its SLDs and to stimulate the Mus81-Mms4 complex [26]. In addition, Esc2 was recently found to promote the degradation of phosphorylated Mms4 [11]. We can Overall, our findings show that the poorly structured N-terminal domain of Eme1 harbors essential regulatory functions of Mus81-Eme1, the control of which appears to be remarkably more elaborate than initially described.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Interestingly, the presumed S. cerevisiae Rad60 ortholog Esc2 has been reported to interact with Mus81 via its SLDs and to stimulate the Mus81-Mms4 complex [26]. In addition, Esc2 was recently found to promote the degradation of phosphorylated Mms4 [11]. We can Overall, our findings show that the poorly structured N-terminal domain of Eme1 harbors essential regulatory functions of Mus81-Eme1, the control of which appears to be remarkably more elaborate than initially described.…”
Section: Discussionsupporting
confidence: 65%
“…Having confirmed by yeast two hybrid that SIM1 and SIM2 are bone fide SIMs that bind SUMO (Fig 5A), the most straightforward assumption would be that they are involved in the control of Mus81-Eme1 by jointly driving the interaction of Eme1 with one or several SUMOylated proteins. They could also drive transient conformational changes through internal interactions between the SIMs of Eme1 and SUMOylated Eme1 or Mus81, which both have been reported to undergo SUMOylation in S. cerevisiae and human cells [11,22,23]. Remarkably, we find that SIM1 and SIM2 fulfil independent functions.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Thus, the isolated MUS81-EME1 and MUS81-EME2 proteins are identical in substrate recognition and endonuclease activities, while their distinct roles in cells could arise See also Figures S4 and S5. ll Article from the cellular temporal controls, such as phosphorylation or association with other regulators (Palma et al, 2018;Princz et al, 2017;Sebesta et al, 2017;Waizenegger et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Vivek et al showed that SUMOylation mediated WRKY33 phosphorylation while disruption of WRKY33 SUMO sites inactivated WRKY33-mediated defense ( 37 ). Waizenegger et al found that Mms4 was engaged by (poly)SUMOylation and targeted for proteasome degradation ( 38 ). Moreover, SUMOylation preserves substrate stability by competing with ubiquitination for the lysine residue or by recruiting the SUMO-targeted ubiquitin ligase (STUBL) family of proteins to the SUMOylated substrates.…”
Section: Process Of Protein Sumoylationmentioning
confidence: 99%